A Preliminary Study of Greenhouse Gases Emissions of Lagos Commercial Vehicles: the Intergovernmental Panel on Climate Change Guidelines at Work - Ahove Michael Adetunji; Okafor Chinenye Lilian; Odewumi Samuel G. (Logistics, Supply Chain, Sustainability and Global Challenges, 2021)
Nigeria deployed Intergovernmental Panel on Climate Change (IPCC) top-down approach which generalizes transport emissions, is not detailed to localize solutions based on sectors. This identified gap was filled using IPCC’s Bottom-Up approach. Quantitative research design was employed using a descriptive survey to determine fuel consumption, vehicle and drivers characteristics through the use of a 30-item instrument named GHG emission estimation instrument (GHGEEI) to estimate the quantity of GHGs from vehicular emissions of commercial road passenger transport activities within the selected routes in Iyana-ipaja, differentiate emission estimates by vehicle categories (Tricycle referred to as ‘Keke’, Shuttle,‘Danfo’14, 18 and 22-seaters) and determine the relative contribution of each commercial road passenger vehicle type according to its age, fuel type, number of engine plugs, and frequency of service. Quota sampling technique was used to identify the strata and their frequency in the population and then convenience sampling was used to select 15% of the quota population for each stratum. Results from the study showed that 10,259.88kg/CO2e, of Carbon dioxide (CO2), 3.65kg/CO2e of Methane (CH4), and 0.58kg/CO2e of Nitrous Oxide (N2O) was emitted daily on the selected areas.